Phenomenological study of the experiences of mothers who have children with autism at SLB Muhammadiyah Bayongbong, Garut Regency - Widadi, Sri Yekti; Puspita, Tantri; Rilla, Eldessa Vava; Alfiansyah, Rudy; Wahyudin, Wahyudin; Aeni, Aksha Zamiatun (Science Midwifery, 2024)
The prevalence of autistic children in Garut Regency in 2022 is 96 people from 14 schools. The number of autistic children at the Bayongbong Special School is 18, of course for children who experience developmental disorders there will be an impact felt by mothers who have autistic children with the emergence of psychological, social and economic burdens. Of course, every mother who has a child with autism will experience different experiences from one mother to another. The aim of this research is to find out what the experiences of mothers who have children with autism are. This research method uses a qualitative method with a phenomenological approach. Sampling was taken using purposive sampling with three informants and data collection techniques in the form of in-depth interviews. The research results obtained 5 themes 1) symptoms of autistic children, 2) informants' feelings when they found out that their child was diagnosed with autism, 3) coping mechanisms, 4) psychologist's burden, 5) extended family support. It is hoped that the results of this research will provide information about the experiences of mothers who have children with autism, be used as supporting data and references in improving the quality of health services for children, and it is hoped that this research can be used as basic data and a source of information or reference for future researchers regarding mothers' experiences. who have children with autism.